Enhanced basal activation of mitogen-activated protein kinases in adipocytes from type 2 diabetes: Potential role of p38 in the downregulation of GLUT4 expression - CARLSON, Christian J; KOTERSKI, Sandra; SCIOTTI, Richard J; POCCARD, German Braillard; RONDINONE, Cristina M (Diabetes (New York, N.Y.), 2003)
Serine and threonine kinases may contribute to insulin resistance and the development of type 2 diabetes. To test the potential for members of the mitogen-activated protein (MAP) kinase family to contribute to type 2 diabetes, we examined basal and insulin-stimulated Erk 1/2, JNK, and p38 phosphorylation in adipocytes isolated from healthy and type 2 diabetic individuals. Maximal insulin stimulation increased the phosphorylation of Erk 1/2 and JNK in healthy control subjects but not type 2 diabetic patients. Insulin stimulation did not increase p38 phosphorylation in either healthy control subjects or type 2 diabetic patients. In type 2 diabetic adipocytes, the basal phosphorylation status of these MAP kinases was significantly elevated and was associated with decreased IRS-1 and GLUT4 in these fat cells. To determine whether MAP kinases were involved in the downregulation of IRS-1 and GLUT4 protein levels, selective inhibitors were used to inhibit these MAP kinases in 3T3-L1 adipocytes treated chronically with insulin. Inhibition of Erk 1/2, JNK, or p38 had no effect on insulin-stimulated reduction of IRS-1 protein levels. However, inhibition of the p38 pathway prevented the insulin-stimulated decrease in GLUT4 protein levels. In summary, type 2 diabetes is associated with an increased basal activation of the MAP kinase family. Furthermore, upregulation of the p38 pathway might contribute to the loss of GLUT4 expression observed in adipose tissue from type 2 diabetic patients.